2014
DOI: 10.1002/art.38338
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Stromal Lymphopoietin, a Novel Proinflammatory Mediator in Rheumatoid Arthritis That Potently Activates CD1c+ Myeloid Dendritic Cells to Attract and Stimulate T Cells

Abstract: Objective. To determine the levels of thymic stromal lymphopoietin (TSLP) and the numbers of TSLP receptor (TSLPR)-expressing CD1c؉ (blood dendritic cell antigen 1-positive) myeloid dendritic cells (MDCs) in the joints as compared with the peripheral blood (PB) of patients with rheumatoid arthritis (RA), as well as to determine the capacity of TSLP to induce MDCdependent T cell activation.Methods. TSLP levels were measured in synovial fluid (SF) samples from patients with RA and those with osteoarthritis (OA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 35 publications
6
41
0
Order By: Relevance
“…Furthermore, these RA SF cDCs are primed to produce TARC as they make it ex vivo without any stimulation (20). TSLP, which is increased in RA SF, was shown to activate cDCs from PB, and TSLP-stimulated PB DCs mimic functional and phenotypic features of intra-articular cDCs, including TARC production (19). In the current study we demonstrate that TARC is increased in SF of RA patients and that MCs from SF are primed to produce TARC.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Furthermore, these RA SF cDCs are primed to produce TARC as they make it ex vivo without any stimulation (20). TSLP, which is increased in RA SF, was shown to activate cDCs from PB, and TSLP-stimulated PB DCs mimic functional and phenotypic features of intra-articular cDCs, including TARC production (19). In the current study we demonstrate that TARC is increased in SF of RA patients and that MCs from SF are primed to produce TARC.…”
Section: Discussionsupporting
confidence: 52%
“…These observations suggest that TARC mediates the migration of pro-inflammatory CCR4-expressing T cells into the joint in RA. Furthermore, it was previously shown that thymic stromal lymphopoietin (TSLP), a strong TARC inducer on cDCs, is increased in the RA SF (19) and that cDCs from the RA SF produce TARC ex vivo (20). The aim of this study was to evaluate TARC levels in SF of RA patients, study the role of cDCs in TARC production in RA joints, and investigate the role of TARC in the attraction of T cells in RA.…”
mentioning
confidence: 99%
“…TSLP has been demonstrated to belong to the innate branch of immunity and to drive, also independently of canonical cytokines, the development of Th9 cells. In relation to this, TSLP levels have been found to be significantly increased in SF of RA patients and capable of stimulating TSLP receptor-expressing CD11c + myeloid dendritic cells to secrete chemokines, causing influx and subsequent activation of CD4 + T cells [7]. The strong connection between IL-9 and autoimmunity has also recently been highlighted by the demonstration of its potential role in T-cell-dependent B-cell differentiation, expansion and antibody production [3].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, blockade of TSLP inhibited arthritis severity in an anti-collagen type II antibody-induced arthritis (CAIA) mouse model [2], and TSLP receptor-deficient mice had less severe arthritis than wild-type mice in T cell-mediated arthritis models [3]. Furthermore, TSLP-primed CD11c 1 myeloid DCs induced Th1 and Th17 activity in addition to Th2 activity in patients with RA [4]. These findings suggest that TSLP plays an important role in the pathophysiology of RA.…”
Section: Introductionmentioning
confidence: 99%